Experimental Study of Thermal Performance of One-Ended Evacuated Tubes for Producing Hot Air. (8th December 2013) - Kumar, Ashish; Kumar, Sanjeev; Nagar, Utkarsh; Yadav, Avadhesh
Abstract : The thermal performance of an evacuated tube solar air collector is experimentally investigated at different air flow rates. Air is used as a working fluid in experimental setup and tested in Indian climatic conditions. The evacuated tube solar air collector consists of fifteen evacuated tubes and manifold channel. The manifold channel consists of a hollow pipe (square pipe) in centre through which air flows. The temperature difference and efficiency are studied with different air flow rates. The reflectors are used to enhance the performance of evacuated tubes solar air collector. It is observed that in case of reflector evacuated tube solar air collector gives higher outlet temperature and temperature difference and has better thermal performance as compared to the case without reflector. The maximum outlet temperature and temperature difference of air are found to be 97.4°C and 74.4°C at a flow rate of 6.70 kg/hr.